West Bank and Gaza - Technical Aassistance in the Passenger Transport Sector Development : Final Report - World Bank (Washington, DC, 2013)
The 2007 transport sector strategy note identified that transportation in the West Bank and Gaza faces extreme challenges, to the extent that mobility for people and goods is severely curtailed, with consequent impacts on the broader functioning of society and the economy. The constraints on personal mobility within the West Bank and Gaza has greatly reduced the market for travel, and hence the business and viability of the transportation sector. Operators are in a loss-making situation and cannot afford fleet renewal, so the quality deteriorates while some buses eventually stop running and some operators go out of business. One strand of the World Bank response to these challenges has been to provide assistance to the Ministry of Transport of the Palestine National Authority (PNA) to develop a practical strategy for action in co-operation with the operator sector. This report presents the main findings and recommendations, and provides a recommended time-bound action plan. The report provides a basis for the policy-makers at the Ministry of Transport to determine the future direction of the sector, and for investors and other stakeholders to consider the possibilities for investment and engagement with the sector.